MAKNA AIR BAGI PETANI TUMPANG SARI DI DESA BAGO, KECAMATAN BESUK, KABUPATEN PROBOLINGGO - Lukman Hadi (Journal of Urban Sociology, 2022)
Bago Village is a village where most of the people work as farmers with an agricultural system that is applied using intercropping techniques. The intercropping system seeks to utilize the available land and is able to produce optimal production. Water politics is a phenomenon that often occurs in the environment of farmers in the process of agricultural irrigation. The meaning of water resources depends on each actor in interpreting the symbols as the basis for their interactions, because each individual will interpret air differently according to his assessment. This research is qualitative research with a phenomenological approach. The technique of making informants uses the purposive sampling technique with the research location in Bago Village, Besuk District, Probolinggo Regency. The results of this study indicate that the meaning of air for agricultural actors is as a shared resource including for the planting process. Water is also basically interpreted as a unifying tool because it has economic, social, and political values in everyday life. Keywords: Irrigation Management; Agricultural Actors; Water Politics; The Meaning of Water